Idiopathic pulmonary hemosiderosis - Say, Burhan; Tınaztepe, Behçet (The Turkish Journal of Pediatrics, 1963)
A case of idiopathic pulmonary hemosiderosis, established by lung biopsy, in an eight year old boy is presented. The unsuccessful use of steroid therapy is reported.